2005
DOI: 10.1021/jf048839b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Pressure and Pulsed Electric Fields on Bioactive Compounds and Antioxidant Activity of Orange Juice in Comparison with Traditional Thermal Processing

Abstract: Bioactive compounds (vitamin C, carotenoids, and flavanones) and DPPH* radical scavenging capacity (RSC) were measured in orange juice (OJ) subjected to different technologies. High pressure (HP) (400 MPa/40 degrees C/1 min), pulsed electric fields (PEF) (35 kVcm(-1)/750 micros), low pasteurization (LPT) (70 degrees C/30 s), high pasteurization (HPT) (90 degrees C/1 min), HPT plus freezing (HPT+F) (-38 degrees C/15 min), and freezing (F) were studied. Among the treatments assayed, even though the losses in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
188
3
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(230 citation statements)
references
References 48 publications
34
188
3
5
Order By: Relevance
“…EPPs content was expressed as mg of gallic acid equivalents (GAE) 100 g-1 dry matter (DM). The method of ferric-reducing antioxidant power (FRAP) assay described by Benzie and Strain (1996), the 2-diphenyl-1-picryhydrazyl (DPPH) radical-scavenging assay described by Sánchez-Moreno et al (2005) and ABTS (2,2-Azinobis-3-ethylbenzotiazoline-6-sulfonic acid) radical scavening essay (RE et al, 1999) were used. A standard curve of Trolox (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid) was employed to estimate the antioxidant capacity as µM Trolox equivalent (µMTE g -1 DM).…”
mentioning
confidence: 99%
“…EPPs content was expressed as mg of gallic acid equivalents (GAE) 100 g-1 dry matter (DM). The method of ferric-reducing antioxidant power (FRAP) assay described by Benzie and Strain (1996), the 2-diphenyl-1-picryhydrazyl (DPPH) radical-scavenging assay described by Sánchez-Moreno et al (2005) and ABTS (2,2-Azinobis-3-ethylbenzotiazoline-6-sulfonic acid) radical scavening essay (RE et al, 1999) were used. A standard curve of Trolox (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid) was employed to estimate the antioxidant capacity as µM Trolox equivalent (µMTE g -1 DM).…”
mentioning
confidence: 99%
“…Sanchez-Moreno et al (2005) reported that cases of thermal treated orange juice (90°C for 1 min) led to an increase in β-cryptoxanthin (19.19 %) and zeaxanthin (37.49 %) and to a decrease in lutein (23.10 %). In this study, concentrations of zeaxanthin (25.75 %), lutein (0.79 %), β-carotene (23.63 %) and β-cryptoxanthin (29.47 %) decreased in the pasteurized lemon juice (p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The following list gives an enumeration of all the measures or procedures investigated: Fruit maturation [130], harvest date [126], storage [5, 126,127], cold storage [125], squeezing [5, 9], pasteurization [5,9,72,120,122], extraction [129], concentration [5], freezing [9,122], freeze-drying [127], light treatment [99], debittering [123], and irradiation [126,127].…”
Section: Aspects Of Postharvest Processing and Storage Proceduresmentioning
confidence: 99%
“…The major flavanones discussed in the relevant publications are the aglycones (hesperetin [9, 122,124] [129,130] and didymin [5,125]) and the neohesperidose glycosides (neohesperidin [124,125], naringin [9, 99, 124 -127] and poncirin [125,127]). The alterations in flavanone glycosides during cold storage (up to 12 or 15 days at 48C) were determined in segments and juice made from grapefruits, mandarin-type fruits, tangelos and oranges [125].…”
Section: Structures Of Individual Compounds Content and Changes In Cmentioning
confidence: 99%
See 1 more Smart Citation